Meningkatkan Benefits melalui Kepuasan Pengguna berdasarkan Kualitas Sistem Informasi Akademik - Muhammad Haris Fadhillah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of this research is to determine the influence of academic information system to benefits through user satisfaction of academic information system in Institut Manajemen Koperasi Indonesia. The research method used is a quantitative method with descriptive approach and verification approach. The sample of this research is 184 students who used academic information system. The measuring instrument used in this research is questionaire with 21 statement items. Data analysis techique using path analysis using software IBM SPS 22.0. Based on the results, (1) user satisfaction is influenced by quality of academic information system, (2) benefits is influenced by user satisfaction, and (3) benefits is influenced by quality of academic information system through user satisfaction.